2019
DOI: 10.1002/jat.3790
|View full text |Cite
|
Sign up to set email alerts
|

Repeated oral dose toxicity study of nickel oxide nanoparticles in Wistar rats: a histological and biochemical perspective

Abstract: Despite the increasing use of nickel oxide (NiO) nanoparticles (NPs), limited information is available on their toxicological effects. Health consequences of 28 days repeated oral exposure to NiO NPs have not been explored thoroughly. Hence, toxicity investigations were performed after 28‐day daily exposure in albino Wistar rats with NiO NPs following Organization for Economic Co‐operation and Development test guideline 407. Histopathology, biochemical indices including oxidative stress and biodistribution pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 75 publications
2
17
1
1
Order By: Relevance
“…Our results are consistent with previous studies suggesting that genotoxicity of NiO NPs is attribute to the oxidative stress induced by excess ROS [60,[65][66][67]. Nanoparticle-induced oxidative stress leads to DNA damage and apoptosis [68].…”
Section: Hamdisupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are consistent with previous studies suggesting that genotoxicity of NiO NPs is attribute to the oxidative stress induced by excess ROS [60,[65][66][67]. Nanoparticle-induced oxidative stress leads to DNA damage and apoptosis [68].…”
Section: Hamdisupporting
confidence: 93%
“…The histological examination confirmed the prominent pathology in different tissues (placenta, liver, kidney, and brain) of pregnant rats and fetuses. These findings are in line with some recent in vivo studies revealed alterations in brain, liver, and kidney tissues [65], and in liver tissues [22]. We suggested that these findings might be attributed to the distribution of NiO NPs and Ni content in all the body organs, NiO NPs could be translocated to other body sites through systemic circulation following oral exposure as reported by Saquib et al,Qi et al,Dumala et al,Yokota et al,Sugamata et al,Jackson et al [22,41,65,[70][71][72].…”
Section: Hamdisupporting
confidence: 93%
“…The present study measured the tissue distribution of Ni NPs by ICP-MS and observed that Ni NPs accumulation in liver tissues in a dose-dependent manner after 28 days of exposure. Nickel nanoparticles’ content disseminates evenly after their exposure to the biological system (Dumala et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The phagocytic cells are linked with the reticuloendothelial system that is involved in NPs sequestration. The dose-dependent accumulation of Ni contents suggested that a higher dose of Ni NPs leads to more absorption and accumulation in the liver (Dumala et al, 2019; Nwokocha et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Показано, в частности, что при ингаляции мышами C57BL/6 НЧ Ni(OH) 2 диаметром до 40 нм в течение 5 ч в дозе 100-900 мкг/м 3 в сонной артерии экспонированных животных снижалась вазоконстрикция под действием фенилэфрина и вазорелаксация в ответ на ацетилхолин. Тем самым даже относительно кратковременная ингаляционная экспозиция Ni-содержащими НЧ вызывает изменения в эндотелии больших сосудов, удаленных от места внедрения наноматериала в организм [38] Подострая пероральная токсичность и биораспределение НЧ NiO размером 13 нм для крыс Wistar были изучены в 28-суточном эксперименте [43]. Отмечены гистопатологические изменения в ряде внутренних органов, рост активности трансаминаз в гомогенатах печени и почек, снижение активности SOD и возрастание активности каталазы.…”
unclassified